Acute Myocarditis and Eculizumab Caused Severe Cholestasis in a 17-Month-Old Child Who Has Hemolytic Uremic Syndrome Associated with Shiga Toxin-Producing Escherichia coli - Yesilbas, Osman; Yozgat, Can Yilmaz; Akinci, Nurver; Sonmez, Sirin; Tekin, Eser; Talebazadeh, Faraz; Jafarov, Uzeyir; Temur, Hafize Otcu; Yozgat, Yilmaz (Journal of Pediatric Intensive Care, 2020)
Cardiovascular involvement is uncommon in pediatric patients with hemolytic uremic syndrome associated with Shiga toxin-producing Escherichia coli (STEC-HUS). In this case report we presented a case of 17-month-old toddler who had a sporadic type of STEC-HUS complicated by acute myocarditis. The patient was successfully treated by a single dose of eculizumab after six doses of therapeutic plasma exchange (TPE) were inefficient to prevent the cardiac complication. Hepatotoxicity was observed after a single dose of eculizumab. Hepatic and cholestatic enzyme levels slowly returned to normal within 6 months. To the best of our knowledge, this is the first case of myocarditis/cardiomyopathy treated with eculizumab in STEC-HUS. This case illustrates the need for vigilance regarding myocardial involvement and eculizumab-induced hepatotoxicity in STEC-HUS.
Keywords: hemolytic uremic syndrome; myocarditis; eculizumab; therapeutic plasma exchange